The Experience of Students undergoing Long Distance Marriage (LDM) in Surabaya - Wakhidah, Umi Widowati; Yusuf, Ah.; Kurnia, Iqlima Dwi (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2020)
Introduction: Long Distance Marriage (LDM) that is undertaken because of having to study outside the area can result in impaired relationship stability due to physical distance and psychological pressure. This study aims to explore the experience of students undergoing LDM at Airlangga University, Surabaya.Method: The study design was a qualitative phenomenological approach, taking data by involving 16 participants who were married and underwent LDM. Participants came from a university in Surabaya. The results of the interviews conducted were then analyzed thematically following the Braun & Clarke framework which consisted of 6 stages including: recognizing data, initializing code, looking for themes, reviewing themes, defining themes and theme names, and producing reports.Results: Five themes that emerged were then used to reflect the objectives of the research conducted, including, 1) the perception of participant marriages based on religion 2) the shadow of participant marriages obtained from parental education when they were little and culture, 3) experience undergoing LDM, consisting of sources of experience and forms of experience 4) reasons for undergoing LDM participants because of continuing education 5) efforts to maintain marital relations include: openness, trust, social support, and coping strategies. Conclusion: Each participant's perceptions and views about the meaning of marriage differ according to their background. Previous experience they have is important for participants because with this experience they can be better prepared to deal with problems while undergoing LDM. The aim and hope of each participant in continuing their education is to improve their lives. Each participant has their own beliefs and ways to maintain relationships during LDM. Marriage relationships must be maintained and maintained by both partners so that peace and happiness will be created in society